Semi-Mechanistic Modeling of Florfenicol Time-Kill Curves and in silico Dose Fractionation for Calf Respiratory Pathogens - Pelligand, Ludovic; Lees, Peter; Sidhu, Pritam Kaur; Toutain, Pierre-Louis (Frontiers in Microbiology, 2019)
An important application of time-kill curve (TKC) assays is determination of the nature of the best PK/PD index (fAUC/MIC or fT%>MIC) and its target value for predicting clinical efficacy in vivo. VetCAST (the veterinary subcommittee of EUCAST) herein presents semi-mechanistic TCK modeling for florfenicol, a long acting (96h) veterinary antimicrobial licensed against calf pneumonia organisms (Pasteurella multocida and Mannheimia haemolytica) to support justification of its PK/PDcut-off and clinical breakpoint. Individual TKC assays were performed with 6 field strains of each pathogen (initial inoculum 107 CFU/ml with sampling at times at 0, 1, 2, 4, 8 and 24 h). Semi-mechanistic modelling (Phoenix NLME) allowed precise estimation of bacteria growth system (KGROWTH, natural growth rate; KDEATH, death rate; BMAX, maximum possible culture size) and florfenicol pharmacodynamic parameters (EMAX, efficacy additive to KDEATH; EC50, potency; Gamma, sensitivity). PK/PD simulations (using present TKC model and parameters of a florfenicol population pharmacokinetic model) predicted the time-course of bacterial counts under different exposures. Out of two licensed dosage regimen, 40 mg/kg administered once was predicted to be superior to 20 mg/kg administered at 48h intervals. Furthermore, we performed in silico dose fractionation with doses 0 – 80 mg/kg administered in 1, 2 or 4 administrations over 96h and for MICs of 0.5, 1, 2, 4 mg/L with 2 inoculum sizes 105 and 107 CFU/mL. Regression analysis (Imax model) demonstrated that i) fAUC/MIC outperformed fT%>MIC as PKPD index and ii) maximum efficacy (IC90%) was obtained when the average free plasma concentration over 96 h was equal to 1.2 to 1.4 times the MIC of Pasteurella multocida and Mannheimia haemolytica respectively.